Cardiac Nuclear Imaging: Current Status and Future Directions - Sun, Zhonghua; Aziz, Aini ab; Md Yusof, Ahmad Khairuddin (Bentham Science Publishers, 2013)
Cardiac single photon emission computed tomography (SPECT) and positron emission tomography (PET) are increasingly being used in the evaluation of patients with suspected or known coronary artery disease by assessing myocardial viability and perfusion and providing invaluable diagnostic and prognostic information. With their capacity to quantify left ventricular function as well as coronary flow reserve, these myocardial perfusion imaging techniques are superior to other methods for the detection of multivessel coronary artery disease and potentially, for risk stratification and prediction of cardiac events. Hybrid SPECT/CT and PET/CT scanners allow identification of flow-limiting coronary lesions and therefore offering great potential for both diagnosis and management. Advances in molecular biology of the cardiovascular system have helped to develop the molecular imaging which may be useful to evaluate targeted molecular and cellular abnormalities in the future. In this review, we will discuss the current state of the art in cardiac nuclear imaging, which include SPECT and PET evaluation of myocardial viability and perfusion. Radiopharmaceuticals used in cardiac SPECT and PET imaging are described, and radiation dose associated with the radiopharmaceuticals is briefly discussed. Clinical applications of hybrid imaging methods in coronary artery disease are presented and future directions are highlighted.